A HETEROTOPOLOGICAL ANALYSIS ON THE NOVEL “ON A DAY LIKE THIS” OF PETER STAMM - Kadir ALBAYRAK (Fırat University, 2019)
The space in which the characters are placed constitutes the basis of the literary work. Due to Switzerland’s geographical and political location, the space in Swiss literature has a different meaning. Switzerland as a land of the Alps, preserves its image of political neutrality and a warless country in the reality as well as in the literary works. In this sense, a spatial analysis of the works of swiss authors is necessary for determining the special situation of space in the Swiss literature. The space plays an important role in the works of Swiss author Peter Stamm. The author tells generally the life stories of the displaced figures in other countries in his works. Stamm’s novel “On a day like this” fits this generalization. Andreas from Switzerland, protagonist of the novel, works as a German teacher in Paris. His monotonous and lonely life away from his family is turned upside down on a health control on which he learns that he has a risk of having lung cancer. After his check, he decides to travel to Switzerland with a young girl named Delphine he met in Paris. After he spends some time there, he sets off to Paris. The novel ends on a beach called Le Grand Crohot on the Atlantic coast, where Andreas hopes to find Delphine. In this analysis of “On a day like this”, the places where Andreas lives and the different places in which he moves through during his travel will be analyzed in the context of the heterotopia concept of Foucault, which represents a different point of view of space. Besides,